Characterization of AMF-diversity of endosphere versus rhizosphere of tea (Camellia sinensis) crops - WU, QIANG-SHENG; SHAO, YA-DONG; GAO, XIU-BING; XIA, TING-JUN; KUÄŒA, KAMIL (The Indian Journal of Agricultural Sciences, 2019)
Tea [Camellia sinensis (L.) Kuntze] crops are globally one of the important commercial crops grown predominantly on acidic soils, a natural ally in form of soil arbuscular mycorrhizal fungi (AMF). The present study was carried out to characterize AMF-diversity in roots and rhizosphere of 20-yr-old Camellia sinensis cv. Yichang Dayecha grown in Xingshan, Hubei, China. Small subunit ribosomal RNA (SSU rRNA) was used to identify the diversity. Tea roots were colonized by native AMF species, with 32.71Â±3.50% of root mycorrhizal colonization. As many 163 and 177 operational taxonomic units (OTUs) were observed in the clone library of rhizosphere soils and roots respectively, suggesting that roots inhabited more AMF species than rhizosphere soils, with as many 111 OUTs overlapped between them. There were only Glomus species and Claroideoglomus / Glomus predominantly observed in roots and rhizosphere soils, respectively, with Glomus Glo20 having highest relative abundance in rhizosphere (>75%) and roots (>25%). Soil and root samples were grouped with the high taxonomic similarity, indicating good group diversity in AMF associated with tea crops.